A study on evaluation of biliary leaks following hydatid liver surgeries - Hanief Mohamed Dar; Mumtazuddin Wani; Mir Mujtaba Ahmmad; Parvaze Salam (Archives of Clinical and Experimental Surgery, 2015)
Background: A high incidence of post-operative bile leaks is reported to be a significant disadvantage of conservative surgical procedures. Materials and Methods: One hundred patients with 180 cysts were operated upon using conservative surgical techniques from May 2007 to November 2009. Results: Post-operative biliary leakage occurred in 26 (26%) patients. Independent clinical predictors for post-operative bile leak were raised alkaline phosphatase and gamma-glutamyl transpeptidase levels (P < 0.05), cyst content being bilious and/or containing pus (P < 0.05), a greater number of cysts (P < 0.05), and radiological appearance of cysts whether, multilocular or degenerated (P > 0.05). Post-operative complications were seen in 21 patients (21%). Complications were seen in 12 of 26 patients with bile leak (46.16%) and in 9 patients among 74 patients (12.16%) without a bile leak (P < 0.05). The mean hospital stay for patients with biliary leakage was 15 days, while the mean hospital stay for patients with no biliary leakage was 8 days. In all patients (22 patients) with low output fistulas (<300 ml/day), the leak was stopped by conservative means in 4 weeks. Among 4 patients with high output fistulas (>300 ml/day), 3 patients were managed conservatively, and in one patient there were no signs of a reduction in bile leakage even after 4 weeks; in this case, endoscopic retrograde cholangiopancreatography with a sphincterotomy was performed, which led to the healing of the fistula 1 week after the endoscopic sphincterotomy. Conclusion: Biliary leakage is common following conservative surgery and is the main cause of post-operative morbidity. Most of the bile leaks can be prevented by thorough inspection of the cavity peroperatively for cyst-biliary communication. Identifying risk factors preoperatively may help to optimize perioperative management. Most bile leaks heal by conservative management. [Arch Clin Exp Surg 2015; 4(2.000): 89-94]